Prostacyclin: An Inflammatory Paradox - Stitham, Jeremiah; Midgett, Charles; Martin, Kathleen; Hwa, John (Frontiers in Pharmacology, 2011)
Prostacyclin (PGI2) is a member of the prostaglandin family of bioactive lipids. Its best-characterized role is in the cardiovascular system, where it is released by vascular endothelial cells, serving as a potent vasodilator and inhibitor of platelet aggregation. In recent years, prostacyclin (PGI2) has also been shown to promote differentiation and inhibit proliferation in vascular smooth muscle cells. In addition to these well-described homeostatic roles within the cardiovascular system, prostacyclin (PGI2) also plays an important role as an inflammatory mediator. In this review, we focus on the contribution of prostacyclin (PGI2) as both a pathophysiological mediator and therapeutic agent in three major inflammatory-mediated disease processes, namely rheumatoid arthritis, where it promotes disease progression (“pro-inflammatory”), along with pulmonary vascular disease and atherosclerosis, where it inhibits disease progression (“anti-inflammatory”). The emerging role of prostacyclin (PGI2) in this context provides new opportunities for understanding the complex molecular basis for inflammatory-related diseases, and insights into the development of current and future anti-inflammatory treatments.